2012
DOI: 10.1021/ac302510g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Surface-Enhanced Resonant Raman Scattering Multiplexing of Biocompatible Gold Nanostars for in Vitro and ex Vivo Detection

Abstract: Surface-enhanced Raman scattering (SERS)-active plasmonic nanomaterials have become a promising agent for molecular imaging and multiplex detection. To produce strong SERS intensity while retaining the non-aggregated state and biocompatibility needed for bioapplications, we integrated near infrared (NIR) responsive plasmonic gold nanostars with resonant dyes for resonant SERS (SERRS). The SERRS on nanostars was several orders of magnitude greater than signals from SERRS on nanospheres and non-resonant SERS on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 35 publications
0
145
0
1
Order By: Relevance
“…BSA, in its denatured form, was found to be more advantageous in that its thiol binding capacity was found to be much stronger and maintained the non-aggregated isolated state of the nanostructures even after multiple washes. In the study by Yuan et al nanoparticle tracking analyses (NTA) confirmed this and also showed that PEG stabilised nanoconstructs tend to form small clusters after multiple washes [9]. The stabilizing property of BSA stems from the exposed thiol groups.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…BSA, in its denatured form, was found to be more advantageous in that its thiol binding capacity was found to be much stronger and maintained the non-aggregated isolated state of the nanostructures even after multiple washes. In the study by Yuan et al nanoparticle tracking analyses (NTA) confirmed this and also showed that PEG stabilised nanoconstructs tend to form small clusters after multiple washes [9]. The stabilizing property of BSA stems from the exposed thiol groups.…”
Section: Resultsmentioning
confidence: 88%
“…Various biopolymers have been reported as stabilisers, but polyethylene glycol (PEG) and bovine serum albumin (BSA) have been recently exploited for their enhanced biocompatibility [9,28]. PEG covering has been shown to stabilise gold nanoparticles and shield the Raman reporter due to the specific adherence on gold nanoparticle's surface that spontaneously forms a monolayer on gold [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhancements on nanostars or nanoaggregates was several orders of magnitude greater than the SERS signals from nanospheres. 40,41 The nanoaggregates yielded large enhancements due to the generation of the EM \hot spots" between two nanospheres. And the highest SERS enhancements had been obtained on aggregates or clusters formed by individual silver or GNPs 20-60 nm in size.…”
Section: Sers Spectra Of Citrate-coated Gnps and Citrate-coated Gnasmentioning
confidence: 99%